The Effect Of Work Motivation And Discipline On Employee Performance At Pt. Arshyndo Nusantara Technique, Tangerang City - Andriani, Jeni; Rahmawati, Risky (ADPEBI, 2022)
This research aims to determine the effect of work motivation and discipline on employee performance at PT. Arshyndo Teknik Nusantara, Tangerang City. The research method used in this research is the Quantitative Method with an associative approach. The sampling technique used is saturated sampling with 53 respondents. Data collection used a questionnaire while data analysis was carried out using analysis of Validity Test, Reliability Test, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test) Correlation Coefficient, Determination Coefficient, Simple Linear Regression Test, Multiple Linear Regression Test, Test Hypothesis (T test and F test). The results of research on employee performance are shown by the multiple linear regression equation Y = 10.908 + 0.443 X1 + 0.292 X2. where the value of the beta coefficient is positive, which means that if motivation and work discipline increase, employee performance will also increase. This is evidenced by the simultaneous hypothesis testing results obtained by the value of Fcount> Ftable (39.895 > 3.18) and reinforced by a significance value of <0.05 (0.000<0.05). The test results of the coefficient of determination of the motivation variable (X1) and work discipline (X2) have an effect of 61.5% on employee performance at PT. Arshyndo Teknik Nusantara. Thus Ho is rejected and H3 is accepted. This means that it is proven that there is a significant effect simultaneously between motivation (X1) and work discipline (X2) on employee performance (Y).